TINJAUAN LITERATUR: KAJIAN EFEKTIVITAS ANTI JAMUR DAUN SIRIH HIJAU & KUNYIT DALAM PENGOBATAN KEPUTIHAN WANITA - Natanael Priltius; Candrika Kumala; Manahan Situmorang; Nova Indah Bakara; Sri Indriyani Sinaga; Febrina Theresa Manurung (Berajah Journal, 2026)
Pathological vaginal discharge is a common reproductive health problem among women, especially in Indonesia, with a prevalence reaching 75%. Conventional treatment for vaginal discharge is often constrained by cost and limited access to healthcare services, making traditional remedies such as green betel leaf decoction and turmeric extract popular alternatives. This study aimed to examine the antifungal effectiveness of green betel leaf decoction and turmeric in significantly reducing pathological vaginal discharge among adolescent to adult women over the long term. The research method employed was a literature review with a systematic search of the Google Scholar database from January 2020 to July 2024 using the keyword “Traditional Medicine for Vaginal Discharge.” From 3,010 initial articles, after screening for duplication and relevance, five articles were selected for descriptive analysis. The results showed that green betel leaf decoction and turmeric extract had high effectiveness in reducing pathological vaginal discharge, as evidenced by a significant decrease in discharge scores (p<0.05) across various age groups of women. Bioactive compounds such as essential oils, flavonoids, and curcumin provide antimicrobial, anti-inflammatory, and immunomodulatory activities that help restore vaginal microflora balance. In conclusion, green betel leaf decoction and turmeric were effective in significantly reducing pathological vaginal discharge among adolescent to adult women, in accordance with the long-term treatment objectives.